MINERAL COMPOSITION OF SOME LATGALE LAKE SEDIMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Our research is focused on sedimentological conditions and postdepositional changes of recent fine grained lake sediments. We used bulk sediment mineralogical composition and grain size distribution as indicators to identify sediment source areas and possible changes during Holocene. We analysed fine grained (clayey) sediments from three Latgale lakes - Zeili, Pauguļi and Plusons, situated in Latgale upland. Lake sediments cover Late Pleistocene glacial deposits – loam and sandy loam. Bulk mineral composition of 6 sediment samples was determined by X-ray diffraction (XRD). Sediments contained typical minerals found in surrounding glacial sediments: rock-forming minerals as quartz, plagioclase, albite, enstatite, dolomite, calcite, and clay minerals - illite, kaolinite. To identify postdepositional changes in lake sediments of Holocene age clay minerals in clay fraction (<2 mkm) should be analysed. Particularly illite, smectite mixed layered minerals - illite/smectite (I/Sm) and chlorite. Additionally, grain size distribution of studied lake sediments was analysed. Accordingly, our studied sediments are clays, silty clays and clayey silts with bimodal particle distribution, except two samples from Zeiļi and Plusons with unimodal distribution.